Pengaruh Gaya Kepemimpinan dan Motivasi Kerja Terhadap Kepuasan Kerja Auditor - Fiki Kartika (Sekolah Tinggi Ilmu Ekonomi SBI, 2012)
This study developed a research model to test the effect of leadership style and motivation to work on job satisfaction auditor. This study uses the path-goal theory developed by Robert House (1971) to explain the impact of the behavior of leaders in subordinate motivation, satisfaction and performance (Luthans, 2006) and the leader is expected to change its behavior to fit the situation, in which the leader is not only to yse force different to defferent subordinate but using different styles to the same subordinates in different situations (Daft, 2001). This research was conducted by questionnaire survey and test the hypothesis of the study wit analiysis Partial Least square (PLS). While sampling using non-probability sampling method with purposive sampling and the sample used is a junior accountant. Based on the results of this study indicate that the style of leadership and motivation positive effect on job satisfaction